Pulse oximetry signal loss during hypoxic episodes in preterm infants receiving automated oxygen control - Langanky, Lukas O.; Kreutzer, Karen Birgit; Poets, Christian F.; Franz, Axel R.; Schwarz, Christoph (European journal of pediatrics, 2024)
The aim of this study was to analyze signal loss (SL) resulting from low signal quality of pulse oximetry-derived hemoglobin oxygen saturation (SpO2) measurements during prolonged hypoxemic episodes (pHE) in very preterm infants receiving …